1993
DOI: 10.1128/iai.61.7.2973-2977.1993
|View full text |Cite
|
Sign up to set email alerts
|

Purification of exfoliative toxin produced by Staphylococcus hyicus and its antigenicity

Abstract: We previously reported the isolation of an exfoliative toxin from culture filtrates of Staphylococcus hyicus (shET) and reproduction of exfoliation in piglets injected with partially purified shET. In this study, we purified shET and compared the biological and physicochemical properties of shET and Staphylococcus aureus exfoliative toxin (sETA and sETB). shET was purified by ammonium sulfate precipitation, DEAE-celulofine A-500 column chromatography, Sephadex G-75 gel filtration, and polyacrylamide gel electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
46
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 13 publications
0
46
0
Order By: Relevance
“…Studies have shown that both virulent and avirulent S. hyicus can be isolated from diseased pigs [1]. The virulent strains produce an approximately 27-kDa [2,3] or 30-kDa [1,4] exfoliative toxin. S. hyicus ex-foliative toxin has been shown to be the factor responsible for the alterations of the skin in EE in pigs [4] and the production of exfoliative toxin correlates with the ability of the strains to induce EE in pigs [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that both virulent and avirulent S. hyicus can be isolated from diseased pigs [1]. The virulent strains produce an approximately 27-kDa [2,3] or 30-kDa [1,4] exfoliative toxin. S. hyicus ex-foliative toxin has been shown to be the factor responsible for the alterations of the skin in EE in pigs [4] and the production of exfoliative toxin correlates with the ability of the strains to induce EE in pigs [5].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with SSSS are usually under the age of 5 years [6] and EE a¡ects piglets in the age of 1^5 weeks, but mild forms of the disease can be observed among older pigs [7]. The histopathological alterations of the skin in the two diseases are similar [6,8] and are in both cases caused by toxins [3,4,9]. SSSS in humans is caused by infection with Staphylococcus aureus producing antigenically distinct exfoliative toxins ETA and ETB, which are the factors that cause exfoliation of the skin [9].…”
Section: Introductionmentioning
confidence: 99%
“…Exudative epidermitis (EE) in pigs is caused by infection with certain strains of Staphylococcus hyicus [1]. Previous studies have shown that the factor responsible for the alterations of the skin in EE is a protein toxin of approximately 27 kDa [2] or 30 kDa [1,3], designated exfoliative toxin. This toxin is produced by virulent strains of S. hyicus [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In the same year, we also reported that piglets and young chickens are susceptible to shET and that shET causes a rounding effect without cell death in the cultured cells (11). Recently, we purified shET from the culture filtrate of S. hyicus strain P-1 by ammonium sulfate precipitation, DEAE-cellulofine column chromatography, Sephadex G-75 gel filtration and polyacrylamide gel electrophoresis (16). We also reported some characteristics of purified shET (16).…”
mentioning
confidence: 95%
“…Recently, we purified shET from the culture filtrate of S. hyicus strain P-1 by ammonium sulfate precipitation, DEAE-cellulofine column chromatography, Sephadex G-75 gel filtration and polyacrylamide gel electrophoresis (16). We also reported some characteristics of purified shET (16). The molecular mass of shET estimated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) is 27,000.…”
mentioning
confidence: 99%